Efeitos da Espironolactona sobre as alterações miocárdicas induzidas pelo hormônio tireoideano em ratos - Fernandes, Maria Luiza Mendonça Pereira (1999)
The relationship between thyroid disease and heart disease has been noted for over 150 years, but only in recent years have the mechanisms involved in thyroid hormone-induced cardiac hypertrophy been studied. In order to study macro and microscopically the morphological changes induced by thyroid hormone and the possible effects of spironolactone on these changes were used 40 Wistar rats, divided into 4 groups, which received .- vehicle used for the dilution of thyroid hormone ( W); levothyroxine sodium at a dose of 50 pg / rat / day (H); spironolactone at a dose of 0.3 mg / kg / day (E) and thyroid hormone and spironolactone (HE) at the doses cited above for 28 consecutive days. All animals were submitted to the following procedures at the beginning and end of the study, weighing, blood collection for hormonal dosages and ECG. At the end of this period the animals were sacrificed to determine left ventricular (LV) weight and to obtain LV sections for histological preparation and morphological analysis. The following results were obtained: 1)Group H lost weight with treatment, group E gained weight and groups C and HE did not change weight. 2)Heart rate was significantly higher in groups H and HE (P <0.01). 3)Doses of T3 and T4 were significantly higher in the groups receiving thyroid hormone (H and HE) (p <0.01). 4)The observed LV weight was significantly higher than the expected weight in the He HE groups (P <0.01). 76 5)Histometric analysis of myocyte diameter measurement revealed that group H had the largest diameter, followed by HE, then E and finally C, with significant differences between all groups (p <0.01). 6)Spironolactone decreased by 14.6% myocyte hypertrophy in the group receiving thyroid hormone and spironolactone (HE group). Increased T3 and T4 levels, weight loss, increased HR, increased LV weight and increased myocyte diameter observed in the treated group. with thyroid hormone reflect the direct and indirect actions of this hormone on the cardiovascular system. Spironolactone has been shown to partially prevent myocardial hypertrophy determined by thyroid hormone by unknown mechanisms. The present study allows to conclude that. D In rats treated with thyroid hormone cardiac hypertrophy occurs with increased LV weight; 2)This hypertrophy is characterized mainly by the increase in myocyte diameter; The . thyroid hormone, is able to prevent 3)Spironolactone, when associated with partially this hypertrophy.